PREVALENSI CACING SALURAN PENCERNAAN SAPI PERAH PERIODE JUNI˗˗JULI 2016 PADA PETERNAKAN RAKYAT DI PROVINSI LAMPUNG - Larasati, Hindun; Hartono, Madi; Siswanto, Siswanto (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2017)
Research held in dairy cattle public farm at Lampung Province on June˗˗July 2016. It is purpose to know gastrointestinal helminths dairy cattle prevalence in public farm at Lampung Province. The research method used was census. Data collection was done by taking all of faecal samples from 125 dairy cattles in public farm at Lampung Province. Data were analyzed descriptively. Faecal samples examination checked with Mc. Master and Sedimentation test. The result indicated that gastrointestinal helminths dairy cattle prevalence at Lampung Province about 21,60%. There are 27 dairy cattles positively infested gastrointestinal helminths. The highest prevalence found in dairy cattle in Bandar Lampung City about 40,00%, while the lowest prevalence found in dairy cattle in Tanggamus Regency about 13,16%. Helminth species that found at Lampung Province are from nematode class (Haemonchus sp., Mecistocirrus sp., Oesophagostomum sp., Cooperia sp., Bunostomum sp.) and trematode class (Paramphistomum sp.). Keywords: Prevalence, Gastrointestinal Helminths, Dairy Cattle, Public Farm